Robotics explained - Bergwall, Bruce; Vuelliquez, Richard; Bergwall Production Inc. (Chadds, Ford PA : Bergwall Productions, 1998)
This video looks at the crucial role that robots are playing in industry, science, the exploration of space and elsewhere.
Keywords: Robotics